POST TRAUMATIC GROWTH PADA PENDERITA KANKER PAYUDARA - Fitri Rahmah, Ade; Listiyanti Widuri, Erlina (HUMANITAS (Jurnal Psikologi Indonesia), 2011)
One of the deadly diseases for women is breast cancer. The wisdomdefined in this study was post traumatic growth. Post traumatic growth is apositive changes experience arising from the struggle of the great crises oflife. The purpose of this study was to determine the growth dynamics ofpost traumatic or post-traumatic growth toward positive life changes andwant to understand further the factors that influence the formation of posttraumatic growth in patients with breast cancer. The method used is basedon qualitative research using phenomenology method. The analysis showedthere were two factors that affecting the aspects of post traumatic growthin patients with breast cancer. External factors are the children andgrandchildren as life expectation and as encouragement or motivationsupport of both parents to perform the treatment, so it eventually leads tothe strengthening of internal factors. Internal factors include the factor offaith (spirituality), a strong desire to recover factors (optimism), resiliencefactors, and reframing factors. There are 4 (four) post traumatic growtharising from the struggle with breast cancer in the face of illness: an increasein spirituality, positive improvement in life, and the higher prosocial andbetter social relations.